ANALISIS KOMPETENSI PAMONG BELAJAR DI SANGGAR KEGIATAN BELAJAR (SKB) JAWA TENGAH - Sukarman, Sukarman (JIV-Jurnal Ilmiah Visi, 2007)
The purpose of this research is to know the correlation of the competence of learning mentors in District Learning Center and the contribution of education level, job experience, training, attitude to the profession and working climate toward the learning mentor’s competence. The population covers 328 learning mentors and the samples include 92 learning mentors from 11 out of 29. The data are collected using questionaires and analyzed using partial correlations and multiply regression techniques. The finding shows, signficant correlations betwen those four variables and the competence of the learning mentors.